Principles of geology an attempt to explain the former changes of the earth's Surface, by reference to causes now in Operation - Lyell, Charles (Cambridge Library Collection - Earth Science, 2010)
In 1830-33, Charles Lyell laid the foundations of evolutionary biology with Principles of Geology, a pioneering book that Charles Darwin took with him on the Beagle. Volume 2 (1832) focuses on plants & animals, & consists of 17 chapters, a comprehensive index & woodcut illustrations of various natural habitats Lyell had observed. The author takes issue with the French biologist Lamarck's theory of the transmutation of species, though Darwin in fact later praised other aspects of Lamarck's work. Lyell examines the connections between the Earth's changing crust & the natural history of many species of birds, insects, mammals & fish. He discusses how wild species physically adapt over time to domestication, the diffusion of plants throughout their specific habitats, geographical distributions of certain types of animals, migratory pattern adaptation due to climate change, & more.